TRANSRADIAL CAROTID STENTING IN A PATIENT WITH BOVINE ARCH ANATOMY - Khan, Muhammad Nadir; Muqaddas, Tahira (Pakistan Armed Forces Medical Journal, 2018)
Carotid artery disease is a major cause of ischemic CVA. We report our experience in stenting of the left internal carotid artery (LICA) in patients with bovine arch, in which right brachiocephalic and left carotid share a common trunk from the aortic arch1.